Mechanical, Microstructural and Tribological Properties of Reactive Magnetron Sputtered Cr–Mo–N Films. Issue 1 (January 2015) - Qi, Dongli; Lei, Hao; Wang, Tiegang; Pei, Zhiliang; Gong, Jun; Sun, Chao
Abstract : The Cr–Mo–N films were deposited on high speed steel (HSS) substrates by a DC reactive magnetron sputtering equipment coupled with two horizontal magnetron sources. The effects of substrate negative bias voltage ( V b ), substrate temperature ( T s ) and gas flow ratio ( R = N2 /(N2 + Ar)) on the microstructure, morphology, as well as the mechanical and tribological properties of the Cr–Mo–N films were investigated by virtue of X-ray diffraction (XRD) analysis, X-ray photoelectron spectroscopy (XPS), field emission scanning electron microscopy (FESEM), atomic force microscopy (AFM), nano-indentation test, ball-on-disk tribometer, and Rockwell indenter et al. With increasing V b to −100 V, the preferred orientation of the films changed from (111) to (200) and their mechanical and tribological properties were improved gradually, too. It was also found that T s gave a significant effect on mechanical property enhancement. When the T s reached 300 °C, the film obtained the highest hardness and effective elastic modulus of approximately 30.1 and 420.5 GPa, respectively and its critical load increased to about 54 N. With increasing R, the phase transformation from body-centered-cubic (bcc) Cr and hexagonal CrMoN x multiphase to single face-centered-cubic (fcc) solid solution phase was observed. The correlations between values of hardness ( H ), effective elastic modulus ( E *), H / E *, H 3 / E * 2, elastic recovery ( W e ) and tribological properties of the films were also investigated. The results showed that the elastic recovery played an important role in the tribological behavior.